Programa nacional de habitação rural no município de Nepomuceno-MG: análise de processos participativos e de conscientização socioambiental - Guedes, Elisângela Zacaroni Pedroso (2023)
To address the housing deficit in Brazil, which includes rural areas of the country, the federal government created the National Rural Housing Program (PNHR) in 2009. The PNHR is part of a social housing policy aimed at providing access to housing for individuals in rural areas facing socio-economic vulnerability. It contributes to the possibility and assurance of rights for people living in rural areas. In this context, this research aims to analyze the implementation of the Rural Housing Program in the southern region of Minas Gerais, specifically in the municipality of Nepomuceno, located in the South/Southwest Mesoregion of Minas Gerais. This region's economy is primarily focused on agriculture, particularly coffee production. Within this context, the research encompasses the National Rural Housing Program, aiming to evaluate elements such as the impacts on the lives of families served by the program and contribute to the evaluation and improvement of this public policy, highlighting potential proposals. At the end of the research process, historical aspects of housing in Brazil, the role of social actors in shaping this policy, as well as the main advancements, challenges, and laws governing the PNHR – including laws, regulations, and decrees – are presented, along with the results obtained with the implementation of the PNHR in the municipality. Through this research, our objective was to analyze the involvement and participation of the AAFAG (Association of Family Farmers of Guapé-MG) and ADESLAGO (Sustainable Development and Housing Agency of Southern Minas) in the planning and execution of actions within the National Rural Housing Program in Nepomuceno-MG. To achieve this, we focused on identifying deficiencies that need to be addressed, aiming to answer questions such as what has been accomplished through the program to date and what is the profile of the families that have truly been assisted. Methodologically, the research had a qualitative, descriptive, and interpretative nature, based on field research. It involved interviews conducted using semi- structured scripts and document research, including legislation, minutes, local and regional public policies. Priority was given to communication with social actors involved in the development and operation of the PNHR, as well as program beneficiaries. Above all, our research aimed to examine the effects of the Social Technical Work of the PNHR on the lives of users concerning environmental awareness and their everyday production of autonomy.